Analisis Status Mutu Air Sungai Sesayap Kabupaten Malinau dengan Metode Storet - Heni Irawati; Encik Weliyadi; Diana Maulianawati; Seprianto Seprianto; Daraisa Daraisa (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2023)
Malinau Kota is one of the Sesayap River basin areas. The Sesayap River is a source of drinking water, transportation routes, and fishing grounds. Many activities around the river flow cause the river to be vulnerable to pollution. Therefore, it is necessary to determine water quality to monitor and manage sustainable water resources. This study aimed to determine the water quality status of the Sesayap River in Malinau Kota, Malinau, North Kalimantan. Water sampling points were three stations; water sampling was carried out eight times. Water samples were measured in situ and ex-situ. Physico-chemical parameters were temperature, salinity, brightness, turbidity, pH, DO, BOD, COD, and ammonia. Data of water quality were analyzed using the Storet method. The water quality standards are based on Government Regulation of the Republic of Indonesia Number 22 of 2021 in Appendix VI of Class I and II River Water Quality Standards. The average temperature measurement results were 27.5 oC, salinity 0 ppt, brightness 12.53 cm, turbidity 196.55 NTU, pH 6.91, DO 5.55 mg/L, BOD 1.96 mg/L, COD 282.17 mg/L and 0.14 mg/L ammonia. The analysis results show that all observation stations are moderately polluted.